FANCA and FANCG are the major Fanconi anemia genes in the Korean population. (12th August 2013) - Park, J; Chung, N‐G; Chae, H; Kim, M; Lee, S; Kim, Y; Lee, J‐W; Cho, B; Jeong, DC; Park, IY
Abstract : Fanconi anemia (FA) is a rare disorder characterized by physical abnormalities, bone marrow failure (BMF), increased risk of malignancies, and cellular hypersensitivity to DNA cross‐linking agents. This study evaluated the genetic alterations in three major Fanconi genes ( FANCA, FANCC, and FANCG ) in 30 FA patients using multiplex ligation‐dependent probe amplification and direct sequencing. Thirteen BMF patients were genetically classified as FA‐A ( n = 6, 46%) and FA‐G ( n = 7, 54%). Four common founder mutations were identified and included two FANCA mutations (c.2546delC and c.3720_3724delAAACA) and two FANCG mutations (c.307+1G>C and c.1066C>T), which had previously been commonly observed in a Japanese FA population. We also detected four novel deleterious mutations: c.2778+1G>C and c.3627‐1G>A of FANCA, and c.1589_1591delATA and c.1761‐1G>A of FANCG . This study shows that mutations in FANCA and FANCG are common in Korean FA patients and the existence of four common founder mutations in an East Asian FA population. Mutation screening workflow that includes these common mutations may be useful in the creation of an international database, and to better understand the ethnic characteristics of FA.